(untitled) (Journal of Universal Science Research, 2025)
This scientific article provides a comprehensive analysis of the complex and multifactorial mechanisms underlying the development of autoimmune diseases and explores the evolution of therapeutic strategies based on immunological principles. The primary objective is to elucidate the breakdown of central and peripheral tolerance that permits self-reactive lymphocytes to activate, proliferate, and mediate tissue damage. The analysis focuses on the interplay of genetic predisposition (e.g., HLA associations, PTPN22), environmental triggers (infections, microbiome dysbiosis, xenobiotics), and immunological effector pathways. Key mechanisms examined include molecular mimicry, epitope spreading, bystander activation, and the critical imbalance between autoreactive effector T cells (Th1, Th17) and regulatory T cells (Tregs). Furthermore, the article systematically reviews the transition from broad-spectrum immunosuppressive therapy (corticosteroids, methotrexate) to targeted biologic agents (anti-TNF, anti-IL-6R, anti-CD20) and small molecule inhibitors (JAK inhibitors). The findings underscore that autoimmune diseases arise not from a single defect but from a convergence of failures across multiple checkpoints of immune regulation. The future of treatment lies in precision medicine approaches that aim to restore immune homeostasis, including antigen-specific tolerance induction and cellular therapies.